RANCANG BANGUN CNC PRINTER 3 DIMENSI MENGGUNAKAN ARDUINO MEGA 2560 - Ramdani, Rizki; Saleh, Agus; Primahidin, Indra (Jurnal TEDC; Vol 18 No 1 (2024): JURNAL TEDC, 2024)
In making this 3 Dimensional CNC Printer machine, the design and construction process is divided into several main parts. The main parts include; design for the mechanical part, design for the frame part, design for the control and calibration system. In the mechanical section, the motor type is selected and the transmission system is designed. The type of motor used is the Stepper Motor Type 17210 G Shinano Kenshi with specifications; angular movement of 1.8 degrees/pulse with a current of 1 A, voltage of 2.6 VDC, resistance of 1.5 Ohm/phase, inductance of 2.8 mH/phase and holding torque of 0.3 Nm. For transmission, it uses a pulley and belt transmission type. The frame uses Tslot 2040, Vslot 2020 and Aluminum Composite materials for the engine mount. In the control and calibration section, this 3 Dimensional CNC Printer machine uses an Arduino Mega 2560. In mechanical testing, movement trials were carried out in the x, y and z axes. The test results show that the movement is as expected. For the x-axis movement, it is 60 mm, the y-axis is 80 mm and the z-axis is 100 mm.